Elite violence and elite numeracy in Europe from 500 to 1900 CE: roots of the divergence - Thomas Keywood; Jörg Baten (Cliometrica, 2020)
Our research expands earlier studies on elite human capital by widening the geographic scope and tracing the early roots of the European divergence. We present new evidence of elite numeracy in Europe since the sixth century CE. During the early medieval period, Western Europe had no advantage over the east, but the development of relative violence levels changed this. After implementing an instrumental variable strategy and a battery of robustness tests, we find a substantial relationship between elite numeracy and elite violence, and conclude that violence had a detrimental impact on human capital formation. For example, the disparities in violence between Eastern and Western Europe helped to shape the famous divergence movement via this elite numeracy mechanism and had substantial implications for the economic fortunes of each region over the following centuries.
Keywords: N00; N13; N33; 330; Elite human capital; Elite violence; Great Divergence; Europe; Middle ages; Early modern period